Perkembangan Pendidikan di Belanda - Lidia Napida; Ummi Kalsum; Dwi Noviani; Zainuddin Zainuddin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Education in the Netherlands is the responsibility of the government and is managed by the Ministry of Education, Culture and Science. The Dutch education system is renowned for its holistic approach, which focuses on overall student development and encourages creativity and critical thinking. Education in the Netherlands is renowned for its comprehensive and progressive system. This education system covers primary, secondary and higher education levels, emphasizes school autonomy, gives teachers the freedom to design learning activities and includes students with diverse needs. The Netherlands also offers many English language study programs at universities, attracting international students. The Dutch education system also emphasizes gender equality and supports diversity in education.